REGULATION PROBLEMS AND THEIR POSSIBLE SOLUTIONS IN THE LITHUANIAN EXPRESS CREDIT SECTOR - Pazniokas, Rimgaudas; Jočienė, Aldona (Ekonomika, 2013)
Abstract. Express credit institutions have started their activities only five years ago when the economic crisis came and increased the borrowing demand. Now, we have the consumer credit law and other legislative acts which aim to ensure this sector regulation. However, there still remain problems that have to be solved. The main of them are inconsistencies in consumers’ solvency evaluation in different companies, the lack of financial knowledge in society and its information, the aggressive lending and advertising policy. The increasing demand for this service shows its importance and proves the necessity to maintain it in the market while at the same time ensuring consumer protection.Key words: express credits, pay-day loans, consumer credit